Innovativeness of the US economy. Permanent or weakening dominance? - Kasperkiewicz, Witold; Rogalski, Wiesław (Comparative Economic Research. Central and Eastern Europe, 2011)
The main purpose of the paper is to analyze the innovativeness of the US economy against those of European and Asian economies. The particular attention was given to the reasons for the forming of the US dominance in the field of innovation. The paper also considers the process of vanishing of American dominance at the end of 1990s. The paper is divided into three parts. In the first one, main causes of American leadership in the field of technology are explained. In the second part, innovation performance of the US economy in comparison with the EU and Asian economies is presented. Finally, there is an analysis of innovation capacity of US economy in the context of challenges resulting from the financial and economic crisis.